2016
DOI: 10.1227/neu.0000000000000994
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Third Ventriculostomy in 250 Adults With Hydrocephalus

Abstract: Use of ETV in adult hydrocephalus has broad application with a low complication rate and reasonably good efficacy in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 73 publications
2
41
0
Order By: Relevance
“…5,43,44,50,56 In other reports with fewer patients, the success rates range from 0% to 100%. 21,23,26,28,31,33,34,48,53,60,64 Whereas some conclude that re-ETV should be considered in all patients who are referred with recurrent symptoms, others mention that re-ETV remains controversial. We think it is worthwhile to give ETV another chance in selected patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,43,44,50,56 In other reports with fewer patients, the success rates range from 0% to 100%. 21,23,26,28,31,33,34,48,53,60,64 Whereas some conclude that re-ETV should be considered in all patients who are referred with recurrent symptoms, others mention that re-ETV remains controversial. We think it is worthwhile to give ETV another chance in selected patients.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Furthermore, as has been extensively reported in the literature on initial ETV, we found that 64% of failures occurred within the first 6 months after re-ETV. 21,26,35,42,53,55,63 Another reason for choosing ETV over shunt treatment is the apparent difference in concern among the parents of children with hydrocephalus. 40 Although the comfort of parents could be a reason to prefer ETV over shunting, it can also make parents less cautious (i.e., provide a false sense of security), as there is no certainty of a cure for hydrocephalus, and late failure of ETV does occur with potential devastating results.…”
Section: Effect Of Timementioning
confidence: 99%
“…The largest series published to date included 250 adult patients for whom the mean follow-up was 6 years. 9 The main indication for ETV in the adult population has been to manage diseases that create obstructive hydrocephalus. While there have been attempts to expand the scope of potential indications for ETV to include nonobstructive hydrocephalic diseases, such as iNPH, [5][6][7] conclusive data are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…9,13,35 Documenting successful treatment of hydrocephalus in a patient with high intracranial pressure is easy to substantiate with this minimal standard, as the outcome of inadequate treatment should be sufficiently obvious because of the underlying life-threatening pathophysiology. It becomes more challenging when patients with chronic hydrocephalus are treated.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…All the patients studied in these research presented intracranial hypertension or other neurological Symptoms, some patients even lost the cognitive competence totally. 8,9) Unfortunately, these repeated insults tend to be neglected. Thus, we aimed to set up an effective approach to treat traumatic brain damage caused by clinical interventions.…”
mentioning
confidence: 99%